PMO-003 Effect of MRI and variable stiffness colonoscopes on caecal intubation rates by experienced endoscopists. (28th May 2012) - Terlevich, A; Maltby, J; Linehan, J
Abstract : Introduction: Magnetic endoscopic imager (MEI) and variable stiffness colonoscopes (VSC) have been shown to improve caecal intubation rates in trainees. Many trained endoscopists in our department prefer to perform colonoscopies with them rather than without. The aim of this study was to assess colonoscopic performance data in experienced endoscopists, with and without the use of MEI and VSC, in our endoscopy department. Methods: Our endoscopy department uses Olympus VSC with MEI in two theatres and standard Pentax colonoscopes with no variation in stiffness or 3D imaging, in our two other theatres. All equipment was purchased in 2009. Experienced endoscopists use both Olympus and Pentax equipment. We have conducted a retrospective case note analysis to assess caecal intubation rates, terminal Ileum intubation rates, polyp detection rates and sedation used, by individual endoscopists. Results: We reviewed 3984 procedures, performed by 16 experienced endoscopists between September 2009 and November 2011. 2598 colonoscopies used Olympus VSC with MEI and 1386 with Pentax equipment. Caecal intubation rate (CIR) was higher in 13/16 endoscopists when using MEI and VSC than without. The total CIR for all colonoscopies was greater using VSC with MEI than without (89.9% vs 87.1%, p=0.0153). There was no significant difference in TI intubation rate, polyp detection rate or sedation used. Conclusion: Although most endoscopists prefer to use MEI and VSC when performing colonoscopy, our data suggests that the difference in caecal intubation rates with experienced endoscopists is small. However, our observed difference in CIR of 2.8% would equate to about 168 colonoscopies in our unit completed, per year that would be otherwise incomplete. Competing interests: None declared.